Fictions of the Real - Werth, Brenda (Michigan State University Press, 2026)
Brenda Werth’s Fictions of the Real traces the transformation of “the real” and its transnational conceptualization by Argentine artists in the twenty-first century, focusing on artists who engage in both documentary theater and filmmaking. Werth places the work of Lola Arias, Romina Paula, Federico León, Mariano Pensotti, and Grupo Krapp in dialogue with the distinct but intertwined lineages of theater and film, exploring the intermedial dimensions of these artists’ theatrical work, resonances in their documentary films, and the transmedial relationships between their documentary plays and films. Focusing on the dynamic and shifting context of Argentina between 1998 and 2023, a period roughly bookmarked by the economic crisis of 2001 and the COVID-19 pandemic, this book explores how these artists disrupt the relations of power and counter political manipulation with their own evocative fictions of the real as they engage in the roles of translators, curators, researchers, archivists, and collaborators.